PENGARUH PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SUZUKI DI PT. SANGGAR MAS JAYA CIBEUREUM-BANDUNG - Haryati, Risna (Universitas Nurtanio Bandung, 2023)
This research focuses on the influence of advertising on the purchasing decisions of Suzuki motorcycles at PT. Sanggar Mas Jaya, Cibeureum-Bandung. In the context of intense competition in the automotive industry, the effectiveness of advertising becomes a key factor that can determine sales success. However, the complexity in determining effective advertising strategies, considering the variations in consumer preferences and their changing behaviors, makes this topic important to research. Using a descriptive verification method with a causal design, data was collected through questionnaires distributed to 99 respondents who are users of Suzuki motorcycles in the PT. Sanggar Mas Jaya area. Data analysis was conducted using simple linear regression techniques, correlation tests, and hypothesis testing to evaluate the relationship between advertising variables and purchasing decisions. The research results indicate that advertising has a positive and significant impact on the purchasing decisions of Suzuki motorcycles at PT. Sanggar Mas Jaya. The level of influence is classified as strong, with advertising contributing 42.2% to the purchasing decision process. The remaining influence is affected by other factors that were not examined in this study. This result emphasizes the importance of effective advertising strategies in boosting sales.